2001
DOI: 10.1046/j.1365-2141.2001.02969.x
|View full text |Cite
|
Sign up to set email alerts
|

Cells from chronic myelogenous leukaemia patients at presentation exhibit multidrug resistance not mediated by either MDR1 or MRP1

Abstract: Summary. Tetramethylrosamine (TMR) is excluded from Pglycoprotein (MDR1)-enriched cell lines, but it stains efficiently MDR1-poor parent lines. Application of the TMR resistance assay to cells obtained from chronic myelogenous leukaemia (CML) patients revealed, in all individuals, a significant resistance compared with healthy donors (P , 0´001). Cells from the same patients at later phases exhibited a further increase in TMR resistance. Doxorubicin was excluded from all cell samples obtained from CML patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 60 publications
3
13
0
Order By: Relevance
“…The possible explanations for these discrepant results may be attributable in part to the different methods used, difference in the various thresholds of positivity and the small number of patients. There are reports in the literature which suggest that ABCC1 does not mediate drug resistance in the cells from CML patients [171], neither does it influence the induction outcome in CML patients [176]. Presently, little is known about the role of ABCG2 in mediating clinical drug resistance that occurs during CML treatment, although an up-regulation of ABCG2 expression was reported in CML CD34 + cell [177].…”
Section: Abc Transporters In Hematological Malignanciesmentioning
confidence: 98%
See 1 more Smart Citation
“…The possible explanations for these discrepant results may be attributable in part to the different methods used, difference in the various thresholds of positivity and the small number of patients. There are reports in the literature which suggest that ABCC1 does not mediate drug resistance in the cells from CML patients [171], neither does it influence the induction outcome in CML patients [176]. Presently, little is known about the role of ABCG2 in mediating clinical drug resistance that occurs during CML treatment, although an up-regulation of ABCG2 expression was reported in CML CD34 + cell [177].…”
Section: Abc Transporters In Hematological Malignanciesmentioning
confidence: 98%
“…The data regarding the relevance of ABCB1 expression in CML patients is controversial. The majority of published data suggest that ABCB1 expression is unlikely to be significantly correlated with prognosis and clinical outcome [162,163,170,171]. However, the results of the other studies in the CML patients suggest that ABCB1 expression may be regarded as an unfavorable prognostic factor in the blastic phase CML [125,164,[172][173][174][175] or CR for the chronic phase CML [176].…”
Section: Abc Transporters In Hematological Malignanciesmentioning
confidence: 99%
“…70 Although no studies have reported ABCG2 expression in CML, one study identified the frequent presence of doxorubicin efflux and resistance in CML samples which was not associated with MDR1 or MRP1-6 expression, suggesting that the presence of another transporter, such as ABCG2 was causing the doxorubicin efflux. 71 In one study of treated and untreated patients with chronic lymphoctyic leukemia (CLL), there was frequent detection of low amounts of ABCG2-mediated efflux, but no correlation was found between ABCG2 activity and previous treatment status, Rai stage or disease progression. 72 Few studies of ABCG2 expression in non-hematologic malignancies have been reported.…”
Section: Abcg2 Expression In Other Malignanciesmentioning
confidence: 99%
“…Classical MDR is characterized by the overexpression of ATP-binding cassette (ABC) drug transporter proteins (1,2). Some of these proteins, such as P-glycoprotein (Pgp, ABCB1, MDR1), multidrug resistance-associated protein (MRP1, ABCC1) and breast cancer resistance protein (BCRP, ABCG2), have been closely related to poor treatment response and prognosis in many malignancies (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%